Defeating dengue a multistakeholder approach to problem solving - Freeman, R. Edward 1951-; Sell, Andrew (Columbia University Press, 2024)
Dengue fever, a mosquito-borne viral infection, is a scourge of tropical climates. An extraordinary project in Indonesia, however, brought together a vast diversity of partners to combat the spread of the disease through innovative methods. This book tells the remarkable story of the fight against dengue and explores the implications for all social enterprises and business families seeking to tackle the world's biggest challenges.R. Edward Freeman and Andrew Sell examine the contributions of the many stakeholders who worked together across national, regional, and local levels for more than a decade. A scientific breakthrough found that infecting mosquitoes with a bacterium could prevent them from transmitting dengue and other viruses. To reduce the toll of the disease, though, this discovery needed to go beyond the laboratory. In Indonesia, thousands of people across a broad swath of society-including a leading business family and its foundation, university and medical school faculty and staff, local volunteers, and the sultan of Yogyakarta-formed a multistakeholder partnership whose efforts ranged from funding and management to large-scale field studies through releasing mosquitoes in their own backyards. Freeman and Sell distill key takeaways about stakeholder engagement, multidisciplinary teamwork, and durable collaboration for readers seeking to implement transformative projects. Defeating Dengue is at once an insightful case study of the power of multistakeholder partnerships and a gripping story of scientific and social achievement.